Potential estimation model in French alpine skiing - Individual evolution curve and progression typology - De Larochelambert, Quentin; Barlier, Kilian; Hamri, Imad; Difernand, Audrey; Sedeaud, Adrien; Toussaint, Jean François; Antero, Juliana; Louis, Pierre-Yves; Coulmy, Nicolas (Frontiers in Physiology, 2023)
Estimating the potential of alpine skiers is an unresolved question, especially because of the complexity of sports performance. We developed a potential estimation model based solely on the evolution of performance as a function of age. A bayesian mixed model allowed to estimate the potential curve and the age at peak performance for the population (24.81 ± 0.2) and for each individual as the uncertainty around this curve. With Gaussian mixtures, we identified among all the estimates four types of curves, clustered according to the performance level and the progression per age. Relying on the uncertainty calculated on the progression curve the model created also allow to estimate a score and an uncertainty associated with each cluster for all individuals. The results allows to : i) describe and explain the relationship between age and performance in alpine skiing from a species point of view (at 0.87%) and ii) to provide to sport staffs the estimation of the potential of each individual and her/his typology of progression to better detect sports potential. The entire methodology is based on age and performance data, but the progression identified may depend on parameters specific to alpine skiing.